THE IDEA OF JAPAN IN MODERN OPERAS: TWO CONTRASTING CASES - Wongsathapornpat, Voraprach (Mahidol Music Journal, 2022)
Two operas set in Japan, Madama Butterfly and Dan-no-Ura, were created over a century apart in very different cultural contexts, one in its composer’s time (early 1900s) and the other in the distant Heian period (in 1185). Although this makes the cultural entity represented in them markedly different, an interesting common thread can be found in many aspects of Japanese culture seen in the two works, from religion to traditional music. This study aims to find new perspectives on these operas through the lens of Japanese culture and to examine the validity of opinions on the topic in current literature. By exploring and comparing these works against their respective historical and social backgrounds, their composers’ source materials and the shared understanding of Japan between them and the audiences, this study hopes to further the discussion of these operas and help inform future performances.